Placenta Accreta Index (PAI) Score Association With Incidence of Placenta Accreta Spectrum, E-Cadherin Expression, Maternal and Neonates Outcome - Martina Wibowo; Agoes Oerip Poerwoko; Raden Soerjo Hadijono; Julian Dewantiningrum; Besari Adi Pramono; Ratnasari Dwi Cahyanti; Dik Puspasari; Hermawan Hermawan (Indonesian Journal of Obstetrics and Gynecology, 2026)
Objective: To evaluated the Placenta Accreta Index (PAI) score for its association with histopathological diagnosis, E-cadherin expression, and clinical outcomes in Placenta Accreta Spectrum (PAS) disorders.Methods: A retrospective cross-sectional analysis was conducted on 81 patients with PAS at a tertiary referral center. Data on PAI scores, histopathology, and maternal/neonatal outcomes were collected. Statistical analysis compared outcomes between patients with PAI scores ≥4 and <4.Results: A PAI score ≥4 was not significantly associated with the final histopathological diagnosis of PAS (p=1.000). E-cadherin expression was lower in PAS tissue, but not significantly correlated with PAI score. However, a PAI score ≥4 was significantly associated with increased intraoperative blood loss (1275 mL vs. 968 mL, p=0.005) and a higher likelihood of requiring blood transfusion (RR 1.56, 95% CI 1.126–2.150, p=0.007). No significant associations were found between PAI score and adverse neonatal outcomes.Conclusion: The PAI score is a practical tool for predicting surgical morbidity, specifically hemorrhage and transfusion risk, in pregnancies clinically suspected of PAS, supporting its use for preoperative planning in resource-limited settings. Its utility as a primary diagnostic marker for histopathological invasion appears limited in a high-risk referral population.Keywords: E-cadherin, maternal outcome, neonatal outcome, placenta accreta spectrum, PAI Score